Incremental feedforward collective pitch control method for wind turbines - Wang, Qinwei; Du, Zeli; Chen, Wenting; Zhang, Jiarui; Lin, Yonggang; Liu, Hongwei (Frontiers in Energy Research, 2023)
The objective of this research is to reduce wind turbine load by pitch control. Based on Light Detection and Ranging (LiDAR) technology and incremental feedforward control theory, an incremental feedforward collective pitch controller is proposed which is based on the wind turbine rotor plane wind disturbance predicted by LiDAR. The controller can be directly superimposed on the traditional collective pitch controller so that incremental pitch angle can fully compensate wind influence. The effectiveness of the controller is verified by multi-software platform joint simulation and hard-ware-in-the-loop experiment. The results show that the controller can effectively reduce the wind turbine power and load fluctuation when the variation trend of wind speed in the rotor plane estimate by LiDAR data is the same as the actual wind speed.